Respon Masyarakat Desa Batu Cermin Dalam Pengembangan Daya Tarik Wisata Gua Batu Cermin, Labuan Bajo - Andriano Calrinto Mami; I Gusti Agung Oka Mahagangga (Program Studi Sarjana Pariwisata, Fakultas Pariwisata, Universitas Udayana, 2020)
The tourist attraction of Batu Cermin Cave is a tourist attraction located in the city center of Labuan Bajo. Attractions offered to tourists who end up in Batu Cermin Cave in the form of natural attractions along the Cave where there are Wisatawaan Stalagtics and Stalagmites who visit Batu Cermin Cave are dominated by tourists from the archipelago. For now the management of Batu Cermin Cave tourist attraction is still managed by the local government in this case is the West Manggarai District Tourism and Culture Service. Later the management of Batu Cermin Cave will involve the Batu Cermin village so that in this study we will discuss